1982
DOI: 10.1021/j100216a028
|View full text |Cite
|
Sign up to set email alerts
|

Test of the entropy basis of the Vogel-Tammann-Fulcher equation. Dielectric relaxation of polyalcohols near Tg

Abstract: ConclusionStudies of the perchlorate anion Raman profiles have proved to be useful in the study of ion-solvent interactions. The use of the perchlorate anion in a ternary system of water and a second electrolyte has often been used to promote ion pairing of the second electrolyte.33,34 However, the assumption that the perchlorate anion is not also involved in ion pairing is not strictly true. The perchlorate anion has also been used as a "noninteracting" anion in (33) T. G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
3
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(111 citation statements)
references
References 7 publications
11
94
3
3
Order By: Relevance
“…There have been a number of detailed discussions concerning the relationship between T 0 and Tfc, the Kauzmann temperature. 15 suggests that B reflects the structure of the material and this would be consistent with the theory since B comprises terms such as the defect-defect correlation length, the defect density, and the defect barrier.…”
Section: Discussionsupporting
confidence: 61%
“…There have been a number of detailed discussions concerning the relationship between T 0 and Tfc, the Kauzmann temperature. 15 suggests that B reflects the structure of the material and this would be consistent with the theory since B comprises terms such as the defect-defect correlation length, the defect density, and the defect barrier.…”
Section: Discussionsupporting
confidence: 61%
“…C [44]. In addition, similar plateau behavior and magnitudes for specific heat and thermal conductivity are observed for a range of tissues [34], again highlighting the value of ultrasound gel as a cryogenic tissue phantom.…”
Section: Resultssupporting
confidence: 52%
“…To explain their observations, Mikosch and Rice suggested that at high viscosities the solvent molecules would form transient cavities through hydrogen bonding. 15,16 The time scale for motion of the liquid ''cage'' would be comparable to or even larger than the Perrin-Stokes-Einstein orientational relaxation time, so a dye molecule could rotate in its cage relatively unperturbed by the liquid. As a result, the orientational relaxation time or at high viscosity would be lower than expected.…”
Section: Resultsmentioning
confidence: 99%
“…12, 13 Mikosch et al, 12 and Rice and Kenney-Wallace 13 proposed that the solvent may form transient cavities due to strong hydrogen bonding interactions. 15,16 The motion of the probe molecules would not be viscously damped but the probe molecules would rotate through large angular steps determined by interactions with the solvent molecules in the nearest neighbor shell. Hence the hydrodynamic properties of the solvent would be of little importance.…”
Section: Introductionmentioning
confidence: 99%